Learning from Families: Pre-Service Teachers’ First Interactions with Parents - Diana Brannon (Networks: An Online Journal for Teacher Research, 2013)
Field experiences are practical ways for pre-service teacher education programs to provide their students experiences and exposure to schools, students, and communities similar to and different from ones that they have attended. The use of field experiences is commonplace in teacher preparation. These experiences provide hands-on application and practical experiences that cannot be replaced or matched by even the best education methods courses (Hammerness, Darling-Hammond, & Bransford, 2007). As Dodds (1989) explains, “Field experiences represent the closest juncture between formal teacher training in universities and on-thejob training in schools” (p. 81). Field experiences have been found to make significant contributions to pre-service teachers’ learning (Ben-Peretz, 1995). These experiences are important for both applying what was learned in the college classroom and learning new things from the process of application and interaction in the field.